Anaerobic digestion of oil-rich solid waste - Thi, Võ Hồng (Vietnam Journal of Biotechnology, 2011)
Among applications of environmental biotechnology for pollution minimization from organic waste, anaerobic digestion has been supposed to be of advantage because of its cost-effectiveness in initial investment as well as operation. Furthermore, capability of energy recovery from biomass thanks to emitted biogas has been evidenced. Nevertheless, anaerobic digestion of oil-rich solid wastes is not always easy and simple since anaerobes are very sensitive to lipid-rich matters as well as to intermediate compounds of oily wastes degradation process. Therefore, the objective of this paper is to systematically draw a profound understanding of steps, the specific characterstics of each step considering both biochemistry and microbial community during anaerobic digestion resulting in the differences between digestion of oil-rich substrates and other organic wastes. That is also basis on which anaerobic treatment of this type of waste can be successfully carried out.